2013
DOI: 10.23986/afsci.7897
|View full text |Cite
|
Sign up to set email alerts
|

The effects of light-emitting diode lighting on greenhouse plant growth and quality

Abstract: The aim of this study is to present the light emitting diode (LED) technology for greenhouse plant lighting and to give an overview about LED light effects on photosynthetic indices, growth, yield and nutritional value in green vegetables and tomato, cucumber, sweet pepper transplants. The sole LED lighting, applied in closed growth chambers, as well as combinations of LED wavelengths with conventional light sources, fluorescent and high pressure sodium lamp light, and natural illumination in greenhouses are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
227
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(268 citation statements)
references
References 51 publications
(83 reference statements)
8
227
0
10
Order By: Relevance
“…Светодиоды могут модулировать рост, развитие и морфогенез растений, влияют на структуру и активность фотосинтетиче-ского аппарата, общий метаболизм, накопление и состав биомассы [3][4][5][6][7][8].…”
Section: исследовали накопление биомассы и качество урожая листового unclassified
“…Светодиоды могут модулировать рост, развитие и морфогенез растений, влияют на структуру и активность фотосинтетиче-ского аппарата, общий метаболизм, накопление и состав биомассы [3][4][5][6][7][8].…”
Section: исследовали накопление биомассы и качество урожая листового unclassified
“…El mejor desarrollo foliar en las plantas evaluadas probablemente se debió al efecto Emerson, ya que bajo los filtros fotoselectivos rojos, las longitudes de onda están en el rango de los 670 a los 700 nm, lo cual supondría un aumento en la tasa de fotosíntesis bajo dicha cobertura. Por otro lado, la luz roja es un componente del espectro visible y este solo hecho es suficiente para que la planta crezca y realice su proceso fotosintético (Lu, et al, 2012, Olle & Virsile, 2013.…”
Section: La Calidad De La Luz Y Su Influencia Sobre El Crecimiento Veunclassified
“…In [4] it was demonstrated that supplemental LED lighting improved the lettuce growth parameters and showed that the photosynthetic utilization efficiency was higher compared to HPS conditions. Experiments on plant growth and development performed with different lighting spectral compositions confirmed that each band of light emission has specific effects on plant physiology and morphology [16]. In [17], blue light influenced leaf morphogenesis, promoting differentiation of mesophyll cells and the formation of intercellular spaces, also having positive effects on leaf thickness and area.…”
Section: Introductionmentioning
confidence: 99%